Targeted Drug Delivery: 2D Layered Double Hydroxide Nanoparticles: Recent Progress toward Preclinical/Clinical Nanomedicine (Small Methods 2/2020). Issue 2 (12th February 2020) - Cao, Zhenbang; Li, Bei; Sun, Luyao; Li, Li; Xu, Zhi Ping; Gu, Zi
Abstract : In article number number 1900343, Zhi Ping Xu, Zi Gu, and co‐workers describe how two‐dimensional layered double hydroxide (LDH) nanoparticles are able to act as "spaceships" to achieve targeted delivery so as to enhance diagnostic/therapeutic efficiency and minimize systemic toxicity. With tunable layered structures and pH‐triggered biodegradability, they can address the critical issues faced in practical nanomedicine through functionalized surface ligands and carried bio‐cargos.